Waste reutilization in pollution remediation: paving new paths for wastewater treatment - D., Suresh; Goh, Pei Sean; Kang, H.S.; Ahmad, Mohammad Norazmi; Ismail, Ahmad Fauzi (Elsevier, 2024)
Given the rising worldwide concern about environmental contamination, there has been a substantial focus on researching sustainable and ecologically friendly materials created from waste. Despite the efforts delving into potentials of recycling or upcycling various waste sources for diverse applications, the sustainable waste reuse and the potential contributions of these wastes in addressing contemporary environmental issues have not been comprehensively analysed and discussed. To close the knowledge gap, this review intends to offer a comprehensive analysis and perspective on the use of three major categories of wastes, namely polymers derived, biomass and non-agricultural waste as renewable sources for pollution remediation specifically in the context of wastewater treatment. Thorough analysis is critical for understanding the potential of waste materials to be reintroduced into profitable usage cycles to decrease the environmental burdens and resource exhaustion. This review covers the sources and properties of the waste materials, as well as the development and performance of the recycled or upcycled materials obtained from these wastes in various applications. The obstacles and future research direction in the field of pollution remediation with waste materials are also presented.